1988
DOI: 10.1111/j.1600-0528.1988.tb01846.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral health concerns of an elderly population in England

Abstract: A group of 437 subjects from a random sample of 737 persons, over 75 yr of age and living independently in the southwest of England, were interviewed about their oral health concerns and desires for dental treatment. Most of the subjects could have received dental treatment without unusual risk, although a third of the sample said they could not move around or attend a dentist without assistance. A dentist had visited the homes of only 2% of the sample, while 22% expressed a desire for this service. Nearly hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 8 publications
(5 reference statements)
3
23
0
Order By: Relevance
“…The results from this study provide further evidence of the discrepancy between clinically determined dental problems, self‐reports of dental problems, and perceived need for dental care. These findings are consistent with previous reports (1, 2, 5, 13–17), which have suggested that self‐evaluations of oral health status rather than disease presence per se , are the primary determinants of perceived need for care. A limitation in the normative measures is that they mainly index disease extent rather than severity, and, thus, may not be associated with either a sign or symptom by the host.…”
Section: Discussionsupporting
confidence: 93%
“…The results from this study provide further evidence of the discrepancy between clinically determined dental problems, self‐reports of dental problems, and perceived need for dental care. These findings are consistent with previous reports (1, 2, 5, 13–17), which have suggested that self‐evaluations of oral health status rather than disease presence per se , are the primary determinants of perceived need for care. A limitation in the normative measures is that they mainly index disease extent rather than severity, and, thus, may not be associated with either a sign or symptom by the host.…”
Section: Discussionsupporting
confidence: 93%
“…The high discrepancy between objecfively assessed and subjectively perceived dental treatment needs suggest that real demand for dental care may be lower than that estimated from objective assessment of dental needs. Similar observations are reported from other surveys (1,7,10,22,25,(30)(31)(32).…”
Section: Discussionsupporting
confidence: 91%
“…Overall, denture-induced oral lesions accounted for 29.8% of the total number of oral lesions. The institutionalized elderly were more frequently edentulous (88.5% when compared with 68% in the non-institutionalized group), while, less than half of them were using dentures (46.5% when compared with 97% in the non-institutionalized group) as a result of the general negligence for their oral health, which in turn, might represent a sign of resignation to physical deterioration (18).…”
Section: Discussionmentioning
confidence: 97%